Feasibility Test of Vlog Media Development With A Science-Edutaiment Approach - Latifah, Diana Rizki; Ahied, Mochammad; Wulandari, Ana Yuniasti Retno; Munawaroh, Fatimatul (UIN Fatmawati Sukarno Bengkulu, 2021)
This research aims to validate the feasibility of VLog media with a science-edutaiment approach. Thisdevelopment research uses the ADDIE model (Analysis, Design, Development, Implementation, andEvaluation). This research was conducted at Bangkalan Public High School 5, a class VII student populationin the Solar System material. The sampling technique used purposive sampling, with a sample of one classVII G. The results showed that the developed profuk could be declared suitable for use with a percentageof media feasibility of 78.6%, feasibility of 92% and an average of 85.3% with very valid category. Based onthese results it can be stated that VLog media is feasible to use